THE EFFECT OF C:H RATIO OF FUEL IN CENTRALLY IGNITED LAMINAR FLAME - YOUSIF IBRAHIM, ALAELDEEN ALTAG (2015)
Laminar burning velocity and Markstein length plays an important role in understanding the behavior of the fuel burning and flame instabilities in the internal combustion engines and different combustors devices. In present work, an experimental configuration was developed to measure the stretched flame propagation speeds, laminar burning velocities, Markstein length, flame thickness and Lewis number of methane, ethane, propane, iso-butane and ethylene-air mixtures at ambient conditions using outwardly spherically expanding flame method. The mixture of gases fuel and air was injected inside the chamber using the partial pressure method, as well as, the equivalence ratio ( ct>) was determined. The main objective of this work is to study the effect of C:H ratio of fuel in laminar burning velocity and flame instabilities at ambient temperature and pressure.